DECISION SUPPORT SYSTEM FEASIBILITY ACCEPTING HOME SURGICAL ASSISTANCE WITH WEIGHT PRODUCT METHOD IN NGABLAK VILLAGE - Arya Eka Saputra; Adi Nugroho (Jurnal Teknik Informatika (Jutif), 2022)
In rural areas, it is very often found that fragile and uninhabitable houses are due to poverty and do not receive housing assistance from the local government. As in Ngablak village, Magelang, there are many people's residences that need to be repaired. The Ngablak village government has created a Home Renovation Assistance program which is one way to protect and prosper residents. To solve the problem in determining the feasibility of receiving home surgery assistance, a Decision Support System was designed using the Weight Product method. The Weight Product method applies a multiplication technique to link the attribute rating and performs the rank first with the weight of the attribute in question. The weighted value for each criterion is used to generate a ranking value in order to make a decision on the candidate for home surgery assistance. Based on calculations using the Weight Product method, the results are in the form of citizen data that has been calculated with the output from the highest to the lowest value. The conclusion of this study is that the existence of a decision support system is very helpful for the Ngablak village government in selecting residents who really deserve assistance in a fast and appropriate way.